Leukocyte O-GlcNAcylation : a novel diagnostic tool for the earlier detection of type 2 diabetes mellitus? - Springhorn, Clare (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.